The Effect Of Health Education Video Of Bullying Behavior On Student’s Knowledge: Health Education Video - Hasbyalloh, Mochamad; Saraswati , Dewi Asri; Atira, Atira (STIKes Mandala Waluya Kendari, 2024)
Background: Bullying is a harmful behavior, especially among elementary school students. Bullying problems and cases that occur must get special attention, so efforts are needed to overcome them. One of the efforts that can be done is through health education using video media. Methods: This research with Quasi experiment approach with pretest- posttest without control group design. Health education was conducted for 10 minutes and repeated 3 times to test the effect of the intervention. The population in this study were all fifthgrade students at SDN Cisarua, West Bandung Regency, to 70 people. This study used a total sampling technique. This research has been conducted at SDN Cisarua, West Bandung Regency, data collection was taken in March 2024. Results: there was an effect of health education with video on bullying behavior on student knowledge. After being given health education there are 50 students with good knowledge, 20 students with sufficient knowledge and no students with poor knowledge. The results of the analysis using the marginal homogeneity test obtained a value of p = 0.0001 <0.05, it can be concluded that Ho is rejected, meaning that there is an effect of health education on the knowledge of respondents. Conclusions: Health education through video media can increase knowledge about bullying on the knowledge of elementary school students.